2016
DOI: 10.1371/journal.pone.0156616
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Success after Stress? Imidacloprid-Induced Hormesis in Males of the Neotropical Stink Bug Euschistus heros

Abstract: Environmental stress in newly-emerged adult insects can have dramatic consequences on their life traits (e.g., dispersion, survival and reproduction) as adults. For instance, insects sublethally exposed to environmental stressors (e.g., insecticides) can gain fitness benefits as a result of hormesis (i.e., benefits of low doses of compounds that would be toxic at higher doses). Here, we experimentally tested whether sublethal exposure to the insecticide imidacloprid would hormetically affect the sexual fitness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 67 publications
3
44
1
Order By: Relevance
“…While our results demonstrate that dietary imidacloprid is not lethal to honey bees at environmentally relevant levels, we emphasize that this should not be taken to mean that it is harmless to bees. We found that dietary imidacloprid produced a hormesis in longevity (days of exposure survived) in honey bees, which is not unexpected; various chemical stressors produce hormesis in insects (37) and imidacloprid itself causes hormetic responses in stink bugs (38), aphids (39) and, notably, in the longevity of spider mites (40). However, the increased longevity that we observed at low doses should be viewed as an intoxication symptom, which is likely to displace affected honey bees from their normal physiological equilibria (37,39).…”
Section: Discussionmentioning
confidence: 53%
“…While our results demonstrate that dietary imidacloprid is not lethal to honey bees at environmentally relevant levels, we emphasize that this should not be taken to mean that it is harmless to bees. We found that dietary imidacloprid produced a hormesis in longevity (days of exposure survived) in honey bees, which is not unexpected; various chemical stressors produce hormesis in insects (37) and imidacloprid itself causes hormetic responses in stink bugs (38), aphids (39) and, notably, in the longevity of spider mites (40). However, the increased longevity that we observed at low doses should be viewed as an intoxication symptom, which is likely to displace affected honey bees from their normal physiological equilibria (37,39).…”
Section: Discussionmentioning
confidence: 53%
“…In Brazil, neonicotinoids and pyrethroids have become the most common insecticides used to control E. heros . The restricted number of chemicals registered for control of these insects and the indiscriminate use of this control practice will certainly lead to substantial biodiversity losses in agricultural landscapes, selection for insecticide‐resistant populations, resurgence and/or outbreaks of insect pests, and impairment of non‐target organisms, including humans …”
Section: Introductionmentioning
confidence: 99%
“…These behavioural responses may vary with the mode of action of the insecticide, or may be mediated by the individual or alterations in the environment. As a consequence, insecticide exposure may be reduced or enhanced (Haynes, ; Guedes et al ., ), with differing effects on each sex and subsequent consequences on sexual fitness, as recently observed in stink bug pests (Haynes, ; Guedes et al ., ; Haddi et al ., ; Tuelher et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…Insecticides used early in soybean production against caterpillars and whiteflies may subsequently interact with Neotropical brown stink bugs that develop later in the season, potentially affecting populations of this pest species and consequently soybean losses. For instance, sublethal exposure to the neonicotinoid imidacloprid and chlorantraniliprole can enhance mating frequency and duration leading to an increase in fitness in this species (Haddi et al ., ; Tuelher et al ., ). Pyriproxyfen and spinosad can also reportedly affect E. heros , but by suppressing the population (Santos et al ., ).…”
Section: Introductionmentioning
confidence: 98%